Implementation of Solving Criminal Cases (Splitsing) in the Proof Process in Criminal Trials - Kamila, Firyal; Yanuar, Iyang; Nurdiansyah, Rizki (Gayaku Publisher, 2022)
The role of a witness who is also an actor in the same case is referred to as a witness who is also a suspect